Speaking Up with Confidence: Affect Perseverance Theory as Pedagogical Tool at High School - Saiful, Saiful (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This research investigates the impact of applying perseverance theory on high school students' speaking skills. Specifically, the intent was to enhance students’ oral performance by fostering persistence, reducing anxiety, and encouraging continuous effort in speaking tasks. This type of research is a pre-experimental design, specifically the one-group pre-test and post-test model. We conducted this research at Public High School 20 Gowa. The study focused on first-grade students, with a total sample of 27 participants selected from the overall population. Speaking ability was measured through three main components: accuracy, fluency, and comprehensibility. The results of the study showed that in the pre-test, students showed low average scores—2.33 in accuracy, 2.14 in fluency, and 2.03 in comprehensibility—resulting in a total mean score of 6.59. After implementing perseverance-based teaching strategies, post-test results showed significant improvement: the average score increased to 3.37 in accuracy, 3.07 in fluency, and 2.85 in comprehensibility, with a total mean score of 92.2. These findings suggest that perseverance theory positively influences students’ speaking performance, not only improving technical aspects of language use but also building their confidence and resilience. Therefore, integrating perseverance theory into speaking instruction can be considered an effective approach to support language development in EFL classrooms.